A field study on the combined use of pre-emergence herbicide and Clearfield® technology for ryegrass management in wheat crops - de Freitas L.F.* (2023)
© (2023), (Southern Cross Publishing). All Rights Reserved.Weed interference in wheat crops are known to cause productivity losses. The objective of this work was to evaluate pre-emergence herbicide application efficiency combined with Clearfield® technology (CL) in ryegrass (Lolium multiflorum) management in wheat crops. A field experiment was conducted from July 2020 to December 2021 using randomized block design in a 2×5 factorial arrangement with four replications. Treatments consisted of combinations of pre-emergence herbicide application - without and with pendimethalin at 1365 g a.i. ha-1 (in 2020 crop season) or without and with pyroxasulfone at 125 g a.i. ha-1 (in 2021 crop season) and post-emergence herbicide application - without application; imazamox at 49, 70, and 91 g a.i. ha-1, or pyroxsulam at 18 g a.i. ha-1. Wheat cultivars used were TBIO Capricho CL® and TBIO Ello CL®. The following characteristics were evaluated: phytotoxicity, ryegrass control, plant height, number of spikes m-2, mean spike weight, 100-grain weight, and grain yield. Treatments phytotoxicity did not exceed 5%, being visible only at 7 DAA, from 14 DAA no injury was observed. The combined application of pre-emergence herbicides pendimethalin or pyroxasulfone with post-emergence herbicides imazamox or pyroxsulam provided superior control of ryegrass than the isolated applications. This management resulted in ryegrass control ranging from 88.8% to 100% in 2020 and from 82.3% to 100% in 2021. In general, grain yield was also higher in treatments with combined pre- and post-emergence applications. The pre-emergence herbicide application in combination with CL technology was effective in managing ryegrass, preventing weed interference, and ensuring the productive potential of wheat crops.